Pengaruh Kepercayaan, Gaya Hidup Dan Pengaruh Sosial Terhadap Minat Penggunaan Shopee Paylater Pada Mahasiswa Fakultas Ekonomi Dan Bisnis Islam UIN STS Jambi - Nur Izzati Maharani; Arsa; Firman Syah Noor (CV. KAMPUS AKADEMIK PUBLISING, 2023)
This thesis is entitled The Effect of Trust, Lifestyle and Social Influence on Interest in Using Shopee Paylater in Students of the Faculty of Economics and Islamic Business UIN Sulthan Thaha Saifuddin Jambi. This study aims to determine the effect of trust, lifestyle and social influence simultaneously and partially on interest in using spaylater in students of the faculty of economics and Islamic business. The method used in this research is descriptive quantitative, where in collecting data researchers use observation, interviews, questionnaires and documentation methods. The number of samples in this study were 96 students. The results showed that trust, lifestyle and social influence had a positive and significant effect on interest in using shopee paylater. Based on data analysis in this study, these variables are valid and reliable. In testing classical assumptions with normal distribution, heteroscedasticity and multicollinearity do not occur. The magnitude of the adjusted R Square value is equal to 77.3%. This means that the variables of trust (X1), lifestyle (X2) and social influence (X3) affect the interest in using shopee paylater by 77.3% while the remaining 22.7% is influenced by other variables outside this regression model.